Analisis Kebijakan Anggaran Program Makan Bergizi Gratis dalam Perspektif Keuangan Negara - Rafi Danang Rasidayu; Aycen Wulung Pilar; Mashur Hasan Bisri (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
The Free Nutritious Meal (MBG) program is a strategic government policy intended to improve students’ nutritional status, prevent stunting, and strengthen Indonesia’s human capital. This study examines the MBG budget policy from a public finance perspective by analysing policy formulation, fiscal governance, accountability, and political economy dynamics affecting its implementation. The study employs a qualitative approach through a literature review of scholarly articles, policy documents, government reports, and relevant publications on nutrition-program financing. The data were analysed thematically through information categorisation, interpretation, and conclusion drawing. The findings indicate that MBG can expand children’s access to nutritious food, support health and education outcomes, and generate long-term benefits for human development. Nevertheless, the programme faces several challenges, including substantial budgetary requirements, risks of mistargeting, limited oversight capacity, and possible political interests influencing priority setting and resource distribution. Its sustainability also depends on synchronised central and local planning, reliable beneficiary databases, and the engagement of businesses and communities. The study concludes that successful MBG implementation requires a realistic, transparent, efficient, and accountable financing design, supported by data-driven oversight and periodic evaluation. These measures are essential to maintain fiscal sustainability, improve programme effectiveness, and ensure that public resources produce equitable nutritional benefits for schoolchildren.